2007
DOI: 10.1523/jneurosci.0572-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Human Muscle Spindle Sensitivity during a Proprioceptive Attention Task

Abstract: The aim of the present study was to test whether fusimotor control of human muscle spindle sensitivity changed when attention was selectively directed to the recognition of an imposed two-dimensional movement in the form of a written symbol.The unitary activities of 32 muscle spindle afferents (26 Ia, 6 II) were recorded by microneurography at the level of the common peroneal nerve. The patterns of firing rate in response to passive movements of the ankle, forming different letters or numbers, were compared in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 33 publications
4
60
2
Order By: Relevance
“…Conversely, in the case in which muscle feedback is given importance, as during the performance of an attention task that relies only on proprioceptive cues, it may be enhanced. More precisely, we recently showed that the fusimotor control of human muscle spindle sensitivity changes when subjects' attention is directed to the recognition of imposed two-dimensional movements in the form of written symbols (Hospod et al 2007). Here again the observed effects seemed to agree with what could be expected for the muscle spindle feedback to be adapted to the ongoing task.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Conversely, in the case in which muscle feedback is given importance, as during the performance of an attention task that relies only on proprioceptive cues, it may be enhanced. More precisely, we recently showed that the fusimotor control of human muscle spindle sensitivity changes when subjects' attention is directed to the recognition of imposed two-dimensional movements in the form of written symbols (Hospod et al 2007). Here again the observed effects seemed to agree with what could be expected for the muscle spindle feedback to be adapted to the ongoing task.…”
supporting
confidence: 58%
“…Later we showed that this ␥-induced activity expressed itself at the level of muscle spindles by selectively changing their sensitivity to movements . Finally, we suggested that the fusimotor drive might be adapted to the ongoing task (Hospod et al 2007). Indeed when the subject is asked to focus attention on an imposed two-dimensional movement (letter or number) to name it, the primary endings tend to become secondary-like, with a depressed dynamic and an enhanced static sensitivity, as compared with a no-attention situation.…”
Section: Discussionmentioning
confidence: 97%
“…We found that target-guided contractions produced more 7-9 Hz coherence among MUs than self-guided contractions, which is consistent with the predicted effects of an increase in the magnitude or gain of afferent feedback. Such a change in afferent feedback and/or fusimotor activity might have stemmed from changes in the cognitive aspects of the task (Hospod et al 2007;Ribot et al 1986;Ribot-Ciscar et al 2000, changes in sympathetic drive (Abila et al 1985), or the change in force dynamics associated with error correction (Marsden et al 1970). Our results suggest that the absence/ presence of a target underlies changes in tremor previously associated with the general absence/presence of visual feedback.…”
Section: Discussionmentioning
confidence: 63%
“…Thus, muscle spindle sensitivity may be affected peripherally (due to thixotropy) and via central nervous system control. 22 Clinically, proprioceptive loss has received considerable attention, particularly in relation to lower-quarter injury, and has been studied most extensively in individuals with anterior cruciate ligament rupture 2,30 and knee osteoarthritis. 4,20,33 Proprioceptive deficits in TDPM have been linked to functional deficiencies, including giving way, 5,31 which has been attributed to knee proprioceptive receptor damage, a sequela of joint injury.…”
Section: T T Resultsmentioning
confidence: 99%
“…Fundamental to this training effect is the increased attention to the task, which is believed to affect muscle spindle sensitivity. 22 Fitzgerald et al 13 developed a training program to promote joint stability in populations with knee pathologies, in which subjects were required to maintain stability following unexpected perturbations. Their findings demonstrated better functional outcomes in a group of subjects with an anterior cruciate ligament-deficient knee following a stint of perturbation training; however, proprioceptive acuity measures were not reported.…”
mentioning
confidence: 99%